DTF Technology Innovation and Community-Based Creative Economy in Tegalsari Religious Tourism Village, Ponorogo - Rooza Meilia Anggraini; Umarwan Sutopo; Roihana Adibah (JARDIRA – Jurnal Pengabdian Digital dan Rekayasa Informatika, 2026)
ABSTRACT Background: Tegalsari Village, a village in Ponorogo Regency, boasts significant religious tourism potential, with the Kiai Ageng Muhammad Besari Mosque and Tomb frequently visited by pilgrims from various regions. However, the village lacks a unique product or souvenir that could attract tourists and positively impact the local economy. Currently, the souvenirs offered are sourced from other sources (wholesale) rather than produced by local residents utilizing existing resources. Contribution: This research aims to develop the creative economic skills of local communities through training in making screen-printed t-shirt souvenirs using the DTF technique as a typical village product. Method: Through the ABCD approach (Asset Based Community-Driven Development), this service program involves community members in identifying and developing potential local assets. Results: The results of the community service show an increase in participants' skills in DTF (Direct to Film) screen printing techniques and enthusiasm for developing independent businesses. Conclusion: This program has the potential to increase village original income and support village autonomy through the use of DTF technology